“Right to Try” Legislation and Its Implications for the FDA Drug Approval Process - Emily Hogan (Washington University Journal of Law & Policy, 2016)
This note analyzes the regulation of experimental drugs by the FDA within the context of “right-to-try” laws. Hogan explores the FDA’s drug approval process, highlighting the specific options for terminally ill patients to fast-track their access to potentially life-saving drugs. Hogan then turns to state “right-to-try” laws, addressing them in relation to federal preemption, pharmaceutical companies, and actual assistance to terminally ill patients. Hogan recommends a relaxation of the FDA’s drug approval process, specifically streamlining the “expanded access” program to give terminally ill patients access to experimental drugs.
Keywords: Right to try; Legislation; FDA; Drug approval process; Federal preemption; Pharmaceutical companies; Terminally ill; Experimental drugs; Regulation